2022
DOI: 10.1021/acsomega.2c01131
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Fracture Height Propagation in Multilayer Formations Considering the Plastic Zone and Induced Stress

Abstract: Hydraulic fracturing and acid fracturing are very effective stimulation technologies and are widely used in unconventional reservoir development. Fracture height, as an essential parameter to describe the geometric size of a fracture, is not only the input parameter of two-dimensional fracturing models but also the output parameter of three-dimensional fracturing models. Accurate prediction of fracture height growth can effectively avoid some risks. For example, petroleum reservoirs produce a large amount of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The patches make the area stronger, while the patches make small patches can improve the change of urban green space and improve the visibility of urban landscape. Referring to the traditional urban green space division method and combining the actual situation, the green space in the study area is divided into four types according to the residential area: small patch (≤1ha), medium patch (1ha-2ha), medium-large patch (2ha-5ha) and large patch (> 5ha), and their areas and numbers are counted respectively (see Table 2 for details) [8]. From Table 2, it can be concluded that the study area has the least amount of green space, accounting for 6%, but the largest area, accounting for 47.57%.…”
Section: Analysis Of Landscape Structure Pattern Of Patches Of Differ...mentioning
confidence: 99%
“…The patches make the area stronger, while the patches make small patches can improve the change of urban green space and improve the visibility of urban landscape. Referring to the traditional urban green space division method and combining the actual situation, the green space in the study area is divided into four types according to the residential area: small patch (≤1ha), medium patch (1ha-2ha), medium-large patch (2ha-5ha) and large patch (> 5ha), and their areas and numbers are counted respectively (see Table 2 for details) [8]. From Table 2, it can be concluded that the study area has the least amount of green space, accounting for 6%, but the largest area, accounting for 47.57%.…”
Section: Analysis Of Landscape Structure Pattern Of Patches Of Differ...mentioning
confidence: 99%
“…For the carbonate reservoir, the main purpose of acidizing is to dissolve some formation rock minerals and plug the materials into pores (fractures) and form acid wormholes with high permeability to communicate between the wellbore and the oil storage medium. , With the continuous exploration and development of carbonate reservoirs, the reservoir conditions faced by acid stimulation become more and more complex, and the shortcomings of traditional acidizing technology become increasingly obvious. This mainly includes the following: (1) The reaction rate of acid–rock is too fast, resulting in uniform dissolution of the rock layer near the well, and it is difficult to form acid wormholes. , (2) When acid is injected, fresh acid continuously washes and dissolves the near well area, causing excessive acidizing, destroying the reservoir structure, seriously affecting the stimulation performance, and even causing borehole collapse. , (3) Some barite cannot undergo nonacid dissolution and cannot achieve the expected effect. (4) The utilization rate of the acid system is low.…”
Section: Introductionmentioning
confidence: 99%
“…This mainly includes the following: (1) The reaction rate of acid–rock is too fast, resulting in uniform dissolution of the rock layer near the well, and it is difficult to form acid wormholes. 6 , 7 (2) When acid is injected, fresh acid continuously washes and dissolves the near well area, causing excessive acidizing, destroying the reservoir structure, seriously affecting the stimulation performance, and even causing borehole collapse. 8 , 9 (3) Some barite cannot undergo nonacid dissolution and cannot achieve the expected effect.…”
Section: Introductionmentioning
confidence: 99%
“…The rock mass of the Shahejie Formation is dense and hard as a whole, but the sand and mudstone interbeds are well developed, and the microfractures are developed on the lithologic interface where sand and mud interbedded . The angle of crossing the thin layer during the drilling process results in the intensification of the mechanical weak plane effect of bedding and fracture. At the same time, the variation of bottom hole exciting pressure under different working conditions aggravates the seepage behavior of the drilling fluid along the bedding fracture and further reduces the effective support effect of drilling a fluid column on the wellbore. These factors have great influence on the wellbore stability during drilling process, which leads to frequent accidents such as downhole collapse and lost circulation and leads to a long construction period, thus seriously hindering the effective exploration and development progress of reservoirs in this area …”
Section: Introductionmentioning
confidence: 99%